Adsorption and desorption of curcumin by poly(vinyl) alcohol-multiwalled carbon nanotubes (PVA-MWCNT) - Zawawi, N. A. (Springer Verlag, 2017)
Carbon nanotubes (CNT) are among the most striking discoveries in the search for new materials as drug delivery carrier. In the present work, multiwalled CNT (MWCNT) functionalized with polyvinyl alcohol (PVA) was developed as a potential carrier for Curcumin (Cur). The aim was to investigate its loading and release efficiency in vitro. To achieve this goal, pristine MWCNT (p-MWCNT) was firstly oxidized by acids and functionalized with PVA. Next, systematic evaluation of Cur loading efficiency on PVA-MWCNT was determined using adsorption kinetics and isotherm studies and was compared to p-MWCNT and oxidized-MWCNT (ox-MWCNT). The release of Cur was analyzed in physiological buffer pH 7.4 and 5.5. From the results, all MWCNT adsorbed Cur rapidly and well described by the pseudo-second order model. The isotherm results suggest that the PVA-MWCNT and p-MWCNT obey Freundlich isotherm model with maximum Cur adsorption (kf) of 5.1 and 69.0 mg/g, respectively, while Cur adsorption on ox-MWCNT followed Langmuir isotherm model with maximum adsorption (qm) of 714.3 mg/g. Cur desorbed significantly (25–30%) from PVA-MWCNT at pH 5.5 than that of pH 7.4, with a sustained release over 3 days of incubation. The results suggest its weak binding interaction to the PVA-MWCNT has facilitated its release at lower pH, compared to ox-MWCNT that occurred via chemisorption. The p-MWCNT ranked the lowest with 4–6% Cur released at both pHs. Overall, the initially developed drug delivery system was considered successful for loading and the release of Cur, which potentially benefit disorders related to cancer or oxidative-related injuries in the future.